Brief communication: Mountain permafrost acts as an aquitard during an infiltration experiment monitored with electrical resistivity tomography time-lapse measurements - M. Pavoni; J. Boaga; A. Carrera; G. Zuecco; G. Zuecco; L. Carturan; M. Zumiani (The Cryosphere, 2023)
Frozen layers within the subsurface of rock glaciers are generally assumed to act as aquicludes or aquitards. So far, this behavior has been mainly defined by analyzing the geochemical characteristics of spring waters. In this work, for the first time, we experimentally confirmed this assumption by executing an infiltration test in a rock glacier of the Southern Alps, Italy. Time-lapse electrical resistivity tomography (ERT) technique monitored the infiltration of 800 L of saltwater released on the surface of the rock glacier; 24 h ERT monitoring highlighted that the injected water was not able to infiltrate into the underlying frozen layer.